Analysis of Distance and Time Traveled in Disaster Evacuation Simulation from Multi-Story Buildings to Assembly Point - Atika Azwa; Salma Bening Naffisa; Zahwa Nurul Latifa; Salma Rihadatul Aisy; Rania Reswanda; Ni Wayan Susila Wati; Bayu Yoni Setyo Nugroho (Universitas Ibn Khaldun Bogor, 2026)
Evacuation preparedness is a critical component in high-rise building safety management, yet empirical data on evacuation times in local contexts remains limited. This study aims to analyze patterns of evacuation time and distance traveled from various points on each floor to the assembly point. Evacuation simulations were conducted in two multi-story buildings involving six measurement points per floor. Building A (2 floors) and Building B (5 floors) generated a total of 42 observations. Results show that evacuation time increases systematically with height: Building A from 28 seconds (floor 1) to 47 seconds (floor 2); Building B from 38.3 seconds (floor 1) to 116 seconds (floor 5). Each additional floor contributes 16-24 seconds to evacuation time. Walking speeds range from 0.97-1.49 m/s with an 18-35% decrease when involving stairs. Individual variability reaches 30-40%, indicating the need for a 40-50% safety margin in planning. Evacuation stairs constitute the primary bottleneck that significantly slows down the evacuation process. These findings provide quantitative benchmarks for evaluating evacuation preparedness and support the strengthening of building safety protocols, particularly for upper-floor occupants who face 3-4 times higher evacuation risks.